Transformasi Spiritual Warga Binaan Kasus Aborsi Melalui Model Pembinaan Berbasis Pesantren Di Lapas Kelas II A Banyuwangi - Safira, Milli; Yohandi; Sulaiman, A. Husam (Jurnal Ilmu Bimbingan dan Konseling, 2025)
This qualitative case study examines the process and outcomes of spiritual transformation experienced by a 21-year-old female inmate (initial S) at Class IIA Banyuwangi Penitentiary, convicted in an abortion case. The study explores her psychological trauma, regret, and strained family relationships, analyzed through a pesantren- or religion-based mentoring model implemented within the correctional institution. Data were collected through in-depth interviews focusing on her religious background, the circumstances of the case, and her experiences during incarceration. The findings reveal that the penitentiary functioned not merely as a place of confinement but as a space for emotional and spiritual reconciliation. S underwent a significant transformation through intensive religious roles and routines, including serving as Head of the Women’s Takmir (Mosollah Annisa) and maintaining consistent congregational worship and recitation practices. These activities fostered spiritual resilience, emotional healing, and a more mature perspective on interpersonal relationships. Socially, incarceration became a source of wisdom (hikmah) that repaired family relationships and restored parental harmony. Additionally, S developed self-reliance through managing the women’s block cooperative, preparing her for post-release independence. This study concludes that structured religion-based mentoring effectively transforms criminal regret into repentance, spiritual growth, and renewed life purpose, highlighting the importance of spiritual programs in correctional rehabilitation.